Caring for child after parental separation: is shared parenting the best solution - Che Soh @ Yusoff, Roslina (2015)
In child custodial disputes, the tremendous shift from parental rights to parental responsibilities throughout the centuries had made the principle of best interests of the child as the utmost matter which the parents and judges must uphold particularly after parental separation. Shared parenting has been considered as one of the factors of best interests principle as it assumes the responsibilities of both parents to have major involvement in the child’s physical care and some form of sharing in the major decision-making. Following divorce or separation, mothers and fathers should retain a strong positive parenting role in their children’s lives. The basis of this concept can be found in the United Nation Convention on Rights of Child which generally emphasizes the importance of both parents to be equally responsible for the upbringing of their children and currently it has been the preferred standard for child custody in many jurisdictions. The custody legislation in Malaysia nevertheless provides no further deliberation on the concept itself. It seems that the concept is developed by the courts through decided cases. Thus, this paper seeks to discuss the extent of the application of shared parenting in resolving custodial disputes by the court after parental separation in Malaysia and determine whether it is the best solution in protecting the child’s best interest. In doing so, it attempts to provide an overview of the approach of the Civil and the Shariah courts in Malaysia in applying the concept. For purposes of comparison, it briefly examines the legislation and the courts practices in Australia on the application of shared parenting since the country has undergone a substantial development in its policy and legislation on this matter. The purpose is to determine the suitability of having a similar shared parenting policy and legislation in Malaysia and to propose amendments to the laws whenever appropriate.